Technological innovation, globalization and the Cold War : a transnational history - Mueller, Wolfgang 1970- Herausgeber; Švík, Peter 1981- Herausgeber (Cold War history, 2023)
This volume focuses on the interconnections between the Cold War, technological innovation and globalization. Although the consequences of globalization have received ample attention in both academia and the public discourse, only limited attention has so far been given to the factors that instigated various waves of this process. This holds particularly true for the period following World War II, during which a struggle between the two global blocs fanned not only technological innovations but also their transfer. This volume is dedicated to examining the links between the Cold War and this phase in the history of globalization, a phase that gradually made the world-despite high levels of international tension-more and more inter-related. More specifically, it anchors a very contemporary phenomenon to its historical context and pinpoints how the varied and multi-layered East-West interactions helped to induce and foster the globalization processes. Emphasizing technology and its cross-bloc flows, as well as several levels of actors, including states, private companies, and individuals, this volume reflects an important shift towards "transnationalism" which has occurred in the historiography in the recent years.This book will be of interest to students of Cold War Studies, science and technology studies, and International Relations